Chronology of dental eruption in a group of Caucasoid mestizos from Cali (Colombia) - de la Cruz, Sebastian; Piedrahita, Alejandra; Sepulveda, Wilmer; Moreno, Freddy; Hernandez, Jesus Alberto (Revista Estomatología, 2017)
Background: The chronological eruption of the deciduous and permanent teeth involves a sequential process that go from the morphogenesis of each tooth to the physiological establishment of the dental occlusion. However, it has been identified that different local and regional genetic and environmental factors can alter the sequential process of eruption of the teeth with respect to the chronological age of human beings.Objective: Characterize the chronology of tooth eruption in a group of Caucasoid mestizos from Cali (Colombia).Materials and Methods: Cross-sectional study that determined sexual dimorphism, arch symmetry and bilateral symmetry from the observation and analysis of the chronology of tooth eruption in 355 panoramic radiographs belonging to a group of Caucasoid mestizos (181 female and 174 men individuals) from the city of Cali (Colombia) through the method of Schour and Massler.Results: When correlating chronological age with radiographic age, no differences between sex, arch and side in the chronology of eruption of the deciduous and permanent teeth were found.Conclusions: The Schour and Massler method showed a high correlation between dental age and chronological age, which is very useful in the dental clinical context to monitor the oral-maxillofacial health in harmony with postnatal growth and development, and in the anthropological and forensic context for the estimation of age as part of the basic identification proceedings and for the documentation of medical-legal age opinion.